Saljuqiylar davri madaniyati – O‘zbek xalqi etnik shakllanishi va madaniyati tarixida o‘g‘uz turkman (saljuqiy) qabilalarining o‘rni - Usmanov Navruz Asanboy o‘g‘li (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
The Seljuks, who appeared on the stage of history at the beginning of the 10th century, were able to establish a large state in a short period of time and rule huge countries with justice. At the top of the Seljuk state was the supreme ruler - the Sultan (Sultan ul-Azam). The throne was inherited from father to son. Distribution of property, land and water, appointment to important state and administrative positions, control of officials' work, etc. were within the scope of the sultan's powers. A sermon was recited in his name and a coin was minted.